Konceptuel litteratur - Serup, Martin Glaz (Passage - Tidsskrift for litteratur og kritik, 2013)
Herefter følger Martin Glaz Serups artikel “Konceptuel litteratur”, der præsenterer en kortlægning af de sidste 10 års konceptuelle litteratur med særlig vægt på dansk poesi. Parallelt med at samtidslyrikken i sin bevægelse i feltet mellem billedkunst og musik nedtoner betydningen af digteren med stort D, er den konceptuelle poesi – og herunder også postproduktionen – med til at flytte opmærksomheden fra kunstens æstetiske niveau til dens idémæssige og materielle forudsætninger. Martin Glaz Serup: “Conceptual literature” This article presents the last ten years of conceptual literature through a series of intertwining movements with a special focus on Danish conceptual literature and how it is embedded in and closely connected to the Nordic and North American scenes. The article gives a brief history of the theoretical background of conceptualism, within both visual art and literature. A discussion of what is (not) conceptual literature unfolds alongside the distinctions made among the related concepts of conceptual literature, poetic documents, post-production and uncreative writing. Furthermore, the article provides both an overview of the most important recent international monographs, anthologies and debates on conceptual literature as well as an attempt to compile a complete list of the full books of conceptual poetry that have been published in Denmark in the last ten years.